Phosphorus uptake and rhizosphere properties of alfalfa in response to phosphorus fertilizer types in sandy soil and saline-alkali soil - Zhang, Tianchan; Wan, Weifan; Sun, Zhi; Li, Haigang (Frontiers in Plant Science, 2024)
Introduction: Phosphorus (P) fertilizer is critical to maintain a high yield and quality of alfalfa (Medicago sativa L.). There are several fertilizer types and soil types in China, and the application of a single type of P fertilizer may not be suitable for present-day alfalfa production. Methods: In order to select the optimal combination of alfalfa and soil type and fertilizer type for improving P utilization efficiency. We conducted a greenhouse pot experiment, calcium superphosphate (SSP), diammonium phosphate (DAP), ammonium polyphosphate (APP), potassium dihydrogen phosphate (KP), and no-fertilizer control treatments were applied to alfalfa in sandy and saline-alkali soils. The response of alfalfa root morphology and rhizosphere processes to different P fertilizers was investigated. Results and discussion: The results showed that shoot biomass of alfalfa was slightly higher in sandy soil than in saline–alkali soil. Shoot biomass of alfalfa increased by 223%-354% in sandy soil under P treatments compared with the control, and total root length increased significantly by 74% and 53% in DAP and SSP treatments, respectively. In saline–alkali soil, alfalfa shoot biomass was significantly increased by 229% and 275% in KP and DAP treatments, and total root length was increased by 109% only in DAP treatment. Net P uptake of alfalfa in DAP treatment was the highest in both soils, which were 0.73 and 0.54 mg plant-1, respectively. Alfalfa shoot P concentration was significantly positively correlated with shoot and root biomass (P < 0.05, 0.01 or 0.001) whereas negatively correlated with acid phosphatase concentration (P < 0.05). Improvement of plant growth and P uptake induced by P fertilizer application was greater in sandy soil than in saline–alkali soil. DAP and KP was the most efficient P fertilizers in both sandy soil and saline–alkali soil.